Status of Isotope Hydrology In Indian Arid Zone - Chandrasekharan, H; Bahadur, Jagdeesh (Annals of Arid Zone, 2016)
The complexity of arid Zone hydrology in the Indian context is outlined and some of the case histories dealing with the investigations on geochronology, groundwater movement, aquifer characteristics, surface/subsurface water inter-relationships. effects of aridity on groundwater recharge, vertical recharge studies and a synthesis of environmental isotopic data are presented. Isotopic techniques could also be utilised to understand precise knowledge on the interconnection between different aquifers. development of salinity and role of palaeowaters in controlling the geohydrology of any region in general and arid zones in particular.